The effect of allyl isothiocyanate on chondrocyte phenotype is matrix stiffness-dependent: Possible involvement of TRPA1 activation - Che, Hui; Shao, Zhiqiang; Ding, Jiangchen; Gao, Hua; Liu, Xiangyu; Chen, Hailong; Cai, Shuangyu; Ge, Jiaying; Wang, Chengqiang; Wu, Jun; Hao, Yuefeng (Frontiers in Molecular Biosciences, 2023)
Osteoarthritis (OA) is a prevalent chronic joint disease with a rising prevalence. Chondrocytes (CHs) are highly differentiated end-stage cells with a secretory phenotype that keeps the extracellular matrix (ECM) balanced and the cartilage environment stable. The CH dedifferentiation causes cartilage matrix breakdown counting as a key pathogenesis of OA. Recently, the activation of Transient receptor potential ankyrin 1 (TRPA1) was claimed to be a risk factor in OA via causing inflammation and ECM degradation. However, the underlying mechanism is still unknown. Due to its mechanosensitive property, we speculated the role of its activation during OA is matrix-stiffness dependent. In this study, we cultured the CHs from OA patients on stiff vs. soft substrates, activated TRPA1 by its agonist, and compared the chondrogenic phenotype, containing cell shape, F-actin cytoskeleton, vinculin, synthesized collagen profiles and their transcriptional regulatory factor, and inflammation related interleukins. The data suggest TRPA1 activation acts as a double-edged sword bringing both good and harmful effects to CHs, and a softer matrix could help to enhance the good one and alleviate the harmful one. Thus, we demonstrate that the effect of TRPA1 activation is controllable by altering the matrix stiffness, which could be a promising strategy for OA treatment.